Vegetable Growers Perception of Pesticide Use Practices and Health Effects in the Vavuniya District - Vijitharan, S.; Loganathan, P. (IDOSI Publications, 2015)
As in developing countries like Sri Lanka, the application of pesticides is often not very precise and unintended exposures occur to other organisms in the general area where pesticides are applied. The objectives of this study were to investigate the current pesticide use pattern and practices in vegetable farming compared with recommended standard and study the health impacts caused by agrochemical in Vavuniya district in Sri Lanka. Primary data was collected from 120 randomly selected farmers among vegetable cultivators in Vavuniyadistrict through questionnaire survey. Primary data were socio-demographic characteristics, pesticide management practices and health impacts. Secondary data were collected from Department of Agriculture and RDHS (Regional Directorate of Health Service) in Vavuniya. The collected data were analyzed using the Pearson correlation test, frequency analysis and crosstabs in SPSS (Statistical Package for Social Sciences), version 16. Almost all farmers depended on synthetic pesticides for the management of pest and 51% of the farmers applied the pesticides 10-20% higher than recommended level. Sixty two percentage of the farmers used banned pesticides and 95% of farmers read the instructions given in the label but they did not follow the label instructions. Around 60% of the farmers harvested the products within seven days though the pre-harvest interval for most vegetable is 14 days. Number of cancer patients increased from 2010 (177 patients) to 2013 (300 patients) in Vavuniya District. Therefore, residual effect of pesticides, over dosage of pesticide usage and poor safety measures may cause kidney disease, cancer and liver failure in this study area.
Keywords: Farmers; Health impacts